Impact des activités touristiques en forêt de Fontainebleau du xixe siècle à nos jours - Micheline Hotyat (Bulletin de l’Association de Géographes Français)
The Fontainebleau forest has attracted many painters through history, especially those of the “Barbizon school”, and it has also been a destination for wealthy Paris inhabitants in search of outdoor activities. Outings to the forest became the fashion and were made easy with the start of train service to Avon in 1849. The Barbizon painters were strong supporters of the majestic oak trees, and in 1861 they won the right to have more than a thousand acres of forest given back to "nature" and to have them called "Artistic Series".These areas have been preserved up to this day, but to what extent have they evolved and what type of landscapes do they offer today? Since World War Two, the Fontainebleau forest has attracted more and more visitors, coming to use the forest area. But this large number of visitors, in such a fragile environment, has led to severe erosion in places making it partly hazardous.Over the centuries, how did administrators balanced the management of the timber production and the welcoming of visitors?